Approximate Identities on Non-Euclidean Manifolds - Hemmat, A. Askari; Fard, Z. Yazdani (Communications in Mathematics and Applications, 2012)
We define a convolution and present a theory for approximate identity on the non-Euclidean manifolds. Here we focus on the hyperboloid and sphere.